Introductory functional analysis : - Reddy, B. Dayanand (Springer, 1998)
This book provides an introduction to functional analysis and treats in detail its application to boundary-value problems and finite elements. The text is distinguished by the fact that abstract concepts are motivated and illustrated wherever possible. Readers of this book can expect to obtain a good grounding in those aspects of functional analysis which are most relevant to a proper understanding and appreciation of the mathematical aspects of boundary-value problems and the finite element method